198k views
5 votes
Can someone show me the answer + how they got there? (x+4)(x-1)

2 Answers

6 votes

Answer: x^2+3x-4

=============================================

Step-by-step explanation:

You can use the FOIL rule to expand out (x+4)(x-1), but here's another way you could do it.

Let y = x+4

This means we replace (x+4) with y to get y(x-1)

Distribute the y term through to get yx-y which can be written as x(y) - 1(y)

After this, replace y with x+4 getting x(x+4)-1(x+4)

Distribute a second time and simplify like so

x(x+4)-1(x+4)

x^2+4x-1x-4

x^2+3x-4

User ChristianF
by
4.3k points
5 votes

Answer:

x^2+3x-4

Step-by-step explanation:

x * x - x + 4x - 4

x^2 - x + 4x - 4

x^2 + 3x - 4

User Callmebob
by
5.1k points